(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
the article states that O’tkir Hoshimov is one of the unique creators of Uzbek literature with his unique prose works, educational works, journalistic works, literary-critical articles, and the writer’s educational, spiritual they will talk about their opinions on education issues.